Factors Related to Routine Visits of Hypertension Patients at Pauh Primary Health Center in 2023 - Yunes, Annisa Ulfa; Yulia, Yulia; Handiny, Febry (Alifah Health Science Symposium Proceeding, 2023)
Hypertension is the main cause of death in the world WHO estimates that 22% in the world and 26.4% of people in Indonesia suffer from hypertension. Hypertension ranks first as a disease with the highest number of visits in the city of Padang. Pauh Health Center is ranked 3rd highest case of hypertension, but with the lowest visit 1%. The purpose of this study was to determine the factors associated with the routine visits of hypertensive patients at the Pauh Health Center.This type of research is quantitative by design cross sectional. The research was conducted at the Pauh Health Center in March - Agust 2023. The population in this study were hypertensive patients who visited the health center. The sampling method used accidental sampling obtained a sample of 65 respondents. The instrument in this study used a questionnaire. Data were analyzed univariately in the form of frequency distribution and bivariately using test Chi-Square.The results showed that 69.2% of respondents did not visit regularly, 56.9% of respondents did not work, 78.5% of respondents suffered from short (1-5 years), 50.8% of respondents received family support, 67.7% of respondents stated that the role of health workers was good. There is a relationship between employment status (p=0.006), length of suffering (p=0.047), family support (p=0.000), role of health workers (p=0.023) routine visits of hypertensive patients at the Pauh Health Center.It is known that there is a relationship between work status, length of suffering, family support and the role of health workers with routine visits to hypertensive patients. It is hoped that this research can be used as evaluation material through the person in charge of non-communicable disease Health Center to provide a visit recording card as a guideline for routine hypertension visits.